1999
DOI: 10.1046/j.1365-2648.1999.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Focus on community: directions for nursing knowledge development

Abstract: Nurses are challenged to advance the theoretical foundations of community practice. This paper offers ideas on what has been done and what needs to be done to meet this challenge. Within a community health nursing perspective, the paper defines community, proposes an integrated knowledge development framework that focuses on community, analyses contemporary theoretical and philosophical foundations of community in nursing, considers three world-views in which nursing can be framed, and examines parameters for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The theoretical diversity of the TAV model is a strength of the model. This diversity is comparable to the theoretical basis of community health nursing knowledge, practice, and research identified by the Association of Community Health Nursing Educators in 1995 (Kulbok et al, 1999). The origin of the TAV model should not be regarded as an internal constraining factor for using the model in practices that involve other ethnic groups.…”
Section: Application Of the Tav Model In Practice Research And Educmentioning
confidence: 55%
See 2 more Smart Citations
“…The theoretical diversity of the TAV model is a strength of the model. This diversity is comparable to the theoretical basis of community health nursing knowledge, practice, and research identified by the Association of Community Health Nursing Educators in 1995 (Kulbok et al, 1999). The origin of the TAV model should not be regarded as an internal constraining factor for using the model in practices that involve other ethnic groups.…”
Section: Application Of the Tav Model In Practice Research And Educmentioning
confidence: 55%
“…Eisner (1991) stated that metaphorical precision is the central vehicle for revealing the qualitative aspects of life. Three metaphors used to conceptualize community and the philosophical basis of community health nursing were the following: machine, biological entity, and melody (Kulbok, Gates, Vicenzi, & Schultz, 1999). As a machine, the community has discrete parts that interact according to certain laws or principles.…”
Section: Theoretical Basis For Tavmentioning
confidence: 99%
See 1 more Smart Citation
“…Kulbok et al. (1999) consider that there must be a focus on the community in addition to the individual as client within nursing models and theories in order to address wider forms of health inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The discipline of nursing is a distinct branch of knowledge developed by a community of scholars with a shared view of the world, who use this perspective to identify phenomena specific to nursing and to guide inquiry into nursing phenomena (Kulbok, Gates, Vicenzi, & Schultz, 1999). Within the discipline of nursing, the public health nursing (PHN) specialty is made up of scholar educators, practitioners, and researchers, who share common concerns about the health conditions of communities and populations, and who acknowledge common approaches to resolving them (Ervin, 2007;Josten, Clarke, Ostwald, Stoskopf, & Shannon, 1995).…”
Section: Scholarly Dialoguementioning
confidence: 99%